THE EFFECT OF EMPLOYEE COMPETENCE AND PERFORMANCE ON COMMUNITY SATISFACTION AT THE PADANG CITY REGIONAL REVENUE AGENCY - Sari, Nadya Dewinta; Susanti, Febsri (LPPM Universitas Bina Bangsa, 2022)
The government continues to strive to provide the best service to the community so that community satisfaction related to the various services that can be provided continues to increase. The community is increasing by continuously improving performance and encouraging employee performance to be more optimal in its implementation. This study aims to analyze and prove the effect of competence and employee performance on community satisfaction at the Padang City Regional Revenue Agency. The method used is descriptive with Multiple Linear Regression analysis technique. The population in the study is all people who make services at the Padang City Regional Revenue Agency in 2020 reaching 1,263. The sampling technique used in this research is simple random sampling. The sample is 93 people. From statistical analysis with the help of SPSS version 23, that: 1) competence has a positive and significant effect on community satisfaction at the Padang City Regional Revenue Agency, and 2) employee performance has a positive and significant effect on community satisfaction at the Padang City Regional Revenue Agency